2019
DOI: 10.3390/molecules24132356
|View full text |Cite
|
Sign up to set email alerts
|

Flowering Stage and Daytime Affect Scent Emission of Malus ioensis “Prairie Rose”

Abstract: Flowering crabapple is an important ornamental flower. It is vital to understand the floral scent properties and the associated release dynamics for carrying out fragrant flower breeding or floral regulation of crabapple. Static headspace solid-phase microextraction coupled with gas chromatography-mass spectrometry was used to detect the volatile compounds in Malus ioensis “Prairie Rose” flowers at different flowering stages and at different day-night time. The results showed that methylheptenone, phenylethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Twenty-four, twenty-two and twenty-two compounds were identified in three Styrax species at three flowering stages, and α-pinene, ocimene and myrcene were common volatiles. The total content of terpenes in S. japonicus revealed a 'V' trend, which was in agreement with the research conducted by Fan et al (2019). However, terpenes content descended continuously in S. grandiflora and S. calvescens.…”
Section: Release Patterns Of Volatile Compounds In Flowers At Three Flowering Stagessupporting
confidence: 90%
“…Twenty-four, twenty-two and twenty-two compounds were identified in three Styrax species at three flowering stages, and α-pinene, ocimene and myrcene were common volatiles. The total content of terpenes in S. japonicus revealed a 'V' trend, which was in agreement with the research conducted by Fan et al (2019). However, terpenes content descended continuously in S. grandiflora and S. calvescens.…”
Section: Release Patterns Of Volatile Compounds In Flowers At Three Flowering Stagessupporting
confidence: 90%
“…The study showed that the main compounds of P. mume cultivars from the four aroma types were phenylpropanoids/benzenoids, which is consistent with many ornamental plants, such as M. ioensis [ 13 ], Rosa odorata and R. chinensis [ 24 ], P . axillaris [ 25 ], and Luculia pinceana [ 26 ].…”
Section: Discussionmentioning
confidence: 56%
“…The floral scent is formed by the interaction of various volatile organic components. In addition, it has been widely accepted that compounds with high OAV contribute more to the aroma of the sample [ 13 , 36 ]. The compounds with higher content and aroma value could be regarded as characteristic components, while the components with lower content and higher odor threshold had a weaker influence on the floral scent [ 2 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations